2009
DOI: 10.1055/s-0029-1243175
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Ischemia Brain Damage Disrupts Brain Cholesterol Homeostasis in Neonatal Rats

Yu Z1,
Li S2,
et al.

Abstract: The present work provides evidence that HI insult destroyed brain cholesterol homeostasis, which might be important in the molecular pathology of hypoxic-ischemic white matter injury. Proinflammatory cytokines insulting oligodendrocytes, may cause cholesterol unbalance. Furthermore, specific therapeutic interventions to maintain brain cholesterol balance may be effective for the recovery of white matter function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…As the most vulnerable oligodendroglial lineage cells, preOLs injury is a hallmark feature of white matter damage induced by hypoxia-ischemia (McTigue et al 2006;Yu et al 2009;Li et al 2010). Consistently, we demonstrated in this study that exposure of OPCs to OGD resulted in cell death as evidenced by increased membrane leakage of LDH, and neonatal pups exposed to hypoxia/ischemia resulted more preOLs damage and decreased in myelin production.…”
Section: Discussionsupporting
confidence: 88%
“…As the most vulnerable oligodendroglial lineage cells, preOLs injury is a hallmark feature of white matter damage induced by hypoxia-ischemia (McTigue et al 2006;Yu et al 2009;Li et al 2010). Consistently, we demonstrated in this study that exposure of OPCs to OGD resulted in cell death as evidenced by increased membrane leakage of LDH, and neonatal pups exposed to hypoxia/ischemia resulted more preOLs damage and decreased in myelin production.…”
Section: Discussionsupporting
confidence: 88%
“…The level of HMGCR was unchanged at 6hr, but increased at 24hr after HI, which might prevent further reduction of cholesterol in the injured hemisphere. The other two studies of neonatal HI in P7 SD rats also reported the diminished cholesterol contents, which lasted longer for 3 days or 3 months following the initial insult ( 13 , 14 ). Disturbance of cholesterol homeostasis after neonatal HI may have adverse consequences on cell survival and brain development.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, cholesterol synthesis is sensitive to reduced O 2 availability and is limited in the conditions of hypoxia-ischemia (HI). This is evidenced by two studies in neonatal HI rats showing chronic loss of brain cholesterol lasting at least 3 days or 3 months following the insults ( 13 , 14 ). Unfortunately, there are no additional investigations on the changes of cholesterol metabolism in response to HI in the immature brain and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…We focused on this region of the brain because the effects of HI are most striking in the hippocampus and overlying cortex in this neonatal HI rat model. This method is widely used to quantify brain damage in such models and has been validated since 1998 (39)(40)(41)(42)(43)(44).…”
Section: Histologymentioning
confidence: 99%